Effect of rearing density on reproduction and embryogenesis of zebrafish Danio rerio (Hamilton, 1922) - Rabbane, Md Golam; Rahman, Md Mizanur; Kabir, Md Alamgir; Faruque, Md Hasan (Dhaka University Journal of Biological Sciences, 2017)
Effect of rearing density (5, 15, 25, 35 and 45 fish/l2) on reproductive performances such as spawning success, fertilization rate, hatching rate and embryogenesis in terms of per cent survival rate of embryos at cleavage, gastrula, segmentation, pharyngula and hatching were evaluated. Survival, hatching, fertilization rate and per cent survivability of embryos did not differ significantly between the treatments 1, 2 and 3, but showed significant difference (p < 0.05) between 4 and 5. Treatment three (25 fish/l2) had five-folds higher number of successful progeny than treatment one. Results suggest that 25 fish/l2 can be used as optimum rearing density. Dhaka Univ. J. Biol. Sci. 26(1): 77-82, 2017 (January)